Issues in Malaysian Higher Education: A Quantitative Representation of the Top Five Priorities, Values, Challenges, and Solutions From the Viewpoints of Academic Leaders - Ghasemy, Majid; Hussin, Sufean; Megat Daud, Megat Ahmad Kamaluddin; Md Nor, Mariani; Ghavifekr, Simin; Kenayathulla, Husaina Banu (SAGE Publications, 2018)
This qualitative inquiry aims at identifying the main issues in Malaysian higher education (HE) system and its sectors from the perspectives of Malaysian academic leaders. For this purpose, four open-ended questions were distributed among 2,786 academic leaders in 25 universities. More than 235 completed questionnaires were collected, containing nearly 4,500 records of priorities, values, challenges, and solutions. Through a quantitative content analysis approach, the records were categorized using the software package ATLAS.ti 7. This resulted to the emergence of 112 categories. Using SPSS 23, the top five categories with maximum frequencies of records were focused for further evaluation. The comparison of the issues in Malaysian HE and its sectors revealed that some of issues were common in all the sectors. In addition, the examination of these categories of data did result to the classification of them into five major categories namely Academic Core Activities, Change and Leadership, Management, Relationships, and Work Values.